2001
DOI: 10.1002/1097-4636(20011205)57:3<413::aid-jbm1184>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the long-term adhesive strength between metal stem and polymethylmethacrylate bone cement by a silica/silane interlayer system

Abstract: A loss of adhesive strength between metal stem and bone cement is clinically found to be a serious problem in total hip arthroplasty and causes many operative revisions. The objective of this study was to improve the long-term adhesive strength at this interface. A new silica/silane interlayer coating system is introduced. The layers are designed to bond the metal stem surface to the polymethylmethacrylate bone cement marginally leakage free. In vitro tensile tests were performed on specimens of TiAl6V4 and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…It is generally accepted that long term durability of cemented THR requires meticulous attention to three elements and two interfaces, which are femoral stem, Great effort has been made to investigate the factors influencing the bond strength at the stem-cement interface, such as increasing stem surface roughness (Chen et al, 1998;Lennon et al, 2003;Ohashi et al, 1998), pre-coating the stem (Fischer et al, 2001;Morita et al, 1997) and utilising "modern cementing techniques" (Geiger et al, 2001;Mulroy Jr. and Harris, 1990). The optimum surface finish of the femoral stem has been the focus of controversy for a long time, mainly concentrating on whether matt stems could accomplish permanent fixation during their in vivo service (Alfaro-Adrian et al, 2001;Shen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that long term durability of cemented THR requires meticulous attention to three elements and two interfaces, which are femoral stem, Great effort has been made to investigate the factors influencing the bond strength at the stem-cement interface, such as increasing stem surface roughness (Chen et al, 1998;Lennon et al, 2003;Ohashi et al, 1998), pre-coating the stem (Fischer et al, 2001;Morita et al, 1997) and utilising "modern cementing techniques" (Geiger et al, 2001;Mulroy Jr. and Harris, 1990). The optimum surface finish of the femoral stem has been the focus of controversy for a long time, mainly concentrating on whether matt stems could accomplish permanent fixation during their in vivo service (Alfaro-Adrian et al, 2001;Shen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…15 In the previous studies, it is reported that surface modification using plasma treatment have improved the bonding strength between heat cured acrylic resin and self-curing acrylic resin. 16,17 The purpose of this study was to evaluate the effect of nonthermal plasma treatment on the bond strength of the autopolymerizing relining resin material to thermoplastic denture base resins in comparison to different surface treatments.…”
Section: 대한치과보철학회지 56권 3호 2018년 7월mentioning
confidence: 99%
“…The corresponding number for the Co alloy was 46%. As a striking feature it should be mentioned that the stability for the Ti alloy was much better than that of the Co alloy [29,30]. …”
Section: Reviewmentioning
confidence: 99%